Antidiarrhoeal activity of rind of Punica granatum (International Current Pharmaceutical Journal, 2013)
Punica granatum (Family: Punicaceae) is a widely consumed fruit in Bangladesh locally known as Anar or Bedana. Traditionally the plant is used to treat diarrhoea, dysentery, hemorrhage, tuberculosis and chronic periodontitis. The present study was undertaken in order to justify and authenticate the traditional use of rind of P. granatum fruit in diarrhoea. Methanolic extract of the rind of the fruit was tested in castor oil- and magnesium sulfate-induced diarrhoea in mice at the doses of 200 and 400 mg/kg body weight. The results of the present study revealed significant antidiarrhoeal activity (p